1998
DOI: 10.1271/bbb.62.1440
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Volatile Compounds from Chungkuk-Jang and Itohiki-Natto

Abstract: Volatile compounds from two South-East Asian fermented soybean foods, Chungkuk-jang (CKJ) and Itohiki-natto (natto), were analysed by gas chromatography-mass spectrometry (GC-MS), gas chromatography (GC), and GC-sniffing. A total of 112 compounds were identified. A large amount of ethanol was detected from CKJ, while acetone and methyl isobutyrate were major components of natto. The characteristic odor compounds of CKJ were some ethyl esters of short chain fatty acids, diallyl disulfide, and several natto-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 9 publications
2
28
0
Order By: Relevance
“…All pyrazines found are also found in fermented soybean curds and have a nutty aroma (5). Because of their abundance, pyrazines are often suggested to be important contributors to the characteristic odor of fermented soybean products such as douchi, hamanatto, natto, sufu and fermented soybean curd (5,13,14). Owens et al (12) reported the degradation of 2,6-dimethylpyrazine during fermentation of roasted, cooked soybean cotyledons.…”
Section: Resultsmentioning
confidence: 99%
“…All pyrazines found are also found in fermented soybean curds and have a nutty aroma (5). Because of their abundance, pyrazines are often suggested to be important contributors to the characteristic odor of fermented soybean products such as douchi, hamanatto, natto, sufu and fermented soybean curd (5,13,14). Owens et al (12) reported the degradation of 2,6-dimethylpyrazine during fermentation of roasted, cooked soybean cotyledons.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, many alkyl esters were identified especially for the fermented soybean products. The presence of the ethyl esters, in particular, has been reported as a "typical" flavor compounds of the fermented soybeans including Chungkukjang and Doenjang (Tanaka et al, 1998;Chung, 1999).…”
Section: Acids and Estersmentioning
confidence: 99%
“…Published by Rynnye Lyan Resources researchers have paid their attention to work on this issue. Numerous reports have described the volatile components in the fermented soybean products; these include Korean Chungkukjang (Tanaka et al, 1998), Natto (Sugawara et al, 1998), and Thua Nao (Leejeerajumnean et al, 2001;Dajanta et al, 2011). Although these studies have shown that the frequent compounds in the fermented soybean products include esters, acids, pyrazines, and phenolic compounds, it should be noted that there are variations of the volatile component profiles among these fermented soybeans mainly depending on the soybean variety, microflora involved, and the processing conditions (Tanaka et al, 1998;Leejeerajumnean et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Around 100 volatile compounds emitted from natto have been identified, 1) indicating the complexity of its specific smell. Tanaka and colleagues 10) have reported that the smell of natto foods was mainly characterized by 10 volatile compounds, including ethanol, 2,3-butanedione (diacetyl), pyrazine, 2-methylpyrazine, 3-hydroxy-2-butanone (acetoin), 2,5-dimethylpyrazine, 2,3,5-trimethylpyrazine, 2-methylpropanic acid (iso-butyric acid), 2-methylbutanoic acid, and 3-methylbutanoic acid (isovaleric acid). Among these compounds, diacetyl and pyrazines are thought to bring out the preferred natto aroma, while the others cause unpleasant and very strong smells that mask the aroma.…”
Section: Identification Of Two Major Ammonia-releasing Reactions Invomentioning
confidence: 99%
“…This odor sometimes causes problems in the quality control of natto products. Ammonia is not usually detected just after the main natto fermentation process, 10) but depending on the conditions of storage, a large amount of ammonia is readily released through excess (so-called secondary) fermentation. Once a natto product is exposed to relatively high temperatures (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) C), secondary fermentation commences to emit ammonia into the air.…”
Section: Identification Of Two Major Ammonia-releasing Reactions Invomentioning
confidence: 99%